The Impact of Cultural Factors on Reading Anxiety of EFL Students - Haerani; Syatriana, Eny; Jumiaty, Andi Asri (PROJECT (Professional Journal of English Education), 2025)
This study investigates the impact of cultural factors on reading anxiety among English as a Foreign Language (EFL) students, focusing on how unfamiliar cultural contexts and linguistic challenges contribute to anxiety levels. Reading is a fundamental skill essential for knowledge acquisition and cognitive development; however, many EFL students experience significant anxiety when engaging with texts in a foreign language. The research involved qualitative analysis through interviews with sixth-semester English education students at Universitas Muhammadiyah Makassar. Findings reveal that while familiar cultural themes, such as batik, can enhance engagement, unfamiliar vocabulary and cultural references often induce anxiety. Most participants expressed a need for additional time and support when encountering texts with unfamiliar cultural elements, particularly regarding the symbolism of motifs like "parang" and "kawung." The results indicate that cultural unfamiliarity significantly contributes to reading anxiety, as students struggle to comprehend texts that require background knowledge of the culture. This study underscores the importance of addressing cultural factors in EFL education to mitigate reading anxiety and improve comprehension, suggesting that increased exposure to cultural contexts may enhance students' reading experiences and reduce anxiety levels.